Drone Brood Homogenate as Natural Remedy for Treating Health Care Problem: A Scientific and Practical Approach - Sidor, Ewelina (Molecules, 2020)
Drone brood homogenate is a little-known bee product used in folk medicine to treat various health problems. It is a very nutritious milky substance with high content of nutrients: proteins, lipids, fatty acids, carbohydrates, vitamins (A, B, E and D), and minerals. Moreover, when collected on early stage of larvae development, it is, most of all, rich source of sex hormone (testosterone, progesterone and estradiol). Some beekeepers consider drone brood as a waste product, although in some countries they use it to fight Varroa. Meanwhile, in many scientific reports a curative effect of bee drone homogenate in treating urgent global health problems have been confirmed, including ovarian dysfunction in women and male infertility, thyroid and immunity disorders, as well as malnutrition in children. A few dietary supplements based on drone brood are available online. Many patents relating to drone brood-based dietary supplements have been filed in Russia, but their prevalence in EU countries is still limited. Further research is needed to fully recognize the pharmacological activity and increase the use of drone brood.